2010
DOI: 10.1186/1471-2474-11-1
|View full text |Cite
|
Sign up to set email alerts
|

The association of spinal osteoarthritis with lumbar lordosis

Abstract: BackgroundCareful review of published evidence has led to the postulate that the degree of lumbar lordosis may possibly influence the development and progression of spinal osteoarthritis, just as misalignment does in other joints. Spinal degeneration can ensue from the asymmetrical distribution of loads. The resultant lesions lead to a domino- like breakdown of the normal morphology, degenerative instability and deviation from the correct configuration. The aim of this study is to investigate whether a relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 40 publications
3
67
1
2
Order By: Relevance
“…Advantages of this method include illuminating the portion of the foot touching the floor. The CatWalk calculates 25 parameters based on footprints and 10 parameters based on time, and for arthritis studies, footprint intensities and areas are the most commonly reported parameters 11, 2629 . As an example, mice with CFA-induced ankle arthritis had less regular gait with changes in speed and duty factor 11 .…”
Section: Spatiotemporal Characterizationmentioning
confidence: 99%
“…Advantages of this method include illuminating the portion of the foot touching the floor. The CatWalk calculates 25 parameters based on footprints and 10 parameters based on time, and for arthritis studies, footprint intensities and areas are the most commonly reported parameters 11, 2629 . As an example, mice with CFA-induced ankle arthritis had less regular gait with changes in speed and duty factor 11 .…”
Section: Spatiotemporal Characterizationmentioning
confidence: 99%
“…3,5,[38][39][40][41][42][43] Most researchers agree that the lumbar lordosis angle positively and strongly associated with spondylolysis and isthmic spondylolisthesis. 5,38,[44][45][46][47] Increasing of the lordosis angle is considered as a risk factor for progression of spondylolysis and ventral displacement of the affected vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal results in the development and progression of lumbar lordosis make spinal osteoarthritis. Degenerative changes in the spine make the loads imposed on the spine distribute abnormally, which will result in the breakdown of the spinal form 12) . This study was intended to examined the relationship between L4-5 HNP and abnormal sagittal spinal alignments; by analysis of the MRIs of an L4-5 HNP patients group and normal adults were analyzed.…”
Section: Discussionmentioning
confidence: 99%